2015
DOI: 10.2807/1560-7917.es2015.20.20.21130
|View full text |Cite
|
Sign up to set email alerts
|

West Nile virus circulation in south-eastern Romania, 2011 to 2013

Abstract: Lineage 2 West Nile virus (WNV), previously found only in sub-Saharan Africa and Madagascar, was identified in Hungary in 2004 and has rapidly expanded in Europe in the past decade. Following a significant outbreak of West Nile fever with neurological cases caused by lineage 1 WNV in Romania in 1996, scattered cases have been recorded in the south-east of the country in each transmission season. Another outbreak, affecting a larger area and caused by lineage 2 WNV, was recorded in 2010. We analysed human sera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 45 publications
(57 reference statements)
1
31
0
Order By: Relevance
“…In 2016, the number of cases increased to 93 with some clustering of disease in the eastern part of the country. Molecular investigations revealed that the viruses involved in cases of 2010 and later years (2011-2013) were related to the Volgograd 2007 strain [29][30][31]. Similar to what seems to have happened in Russia; cases between 2014 and 2016 are likely to have been caused by the overwintering of the strain that was detected in Romania in previous years.…”
Section: Flaviviruses (Genus Flavivirus Family Flaviviridae)mentioning
confidence: 82%
“…In 2016, the number of cases increased to 93 with some clustering of disease in the eastern part of the country. Molecular investigations revealed that the viruses involved in cases of 2010 and later years (2011-2013) were related to the Volgograd 2007 strain [29][30][31]. Similar to what seems to have happened in Russia; cases between 2014 and 2016 are likely to have been caused by the overwintering of the strain that was detected in Romania in previous years.…”
Section: Flaviviruses (Genus Flavivirus Family Flaviviridae)mentioning
confidence: 82%
“…Although several other collected mosquito species (e.g., An. hyrcanus) have been found positive for WNV-RNA in Romania [11,13,24], members of the Culex pipiens complex are considered the main vectors for WNV in both urban and rural/natural transmission cycles [13].…”
Section: Discussionmentioning
confidence: 99%
“…Various outbreaks of WNV infections have been reported in southern and southeastern Europe, resulting in several thousand human cases with dozens of fatal outcomes [8,9]. Thereby, Romania is a hotspot for WNV circulation [6,8,[10][11][12][13][14]. Over the last two decades, the country has experienced at least three large outbreaks of WNV (1996,2010,2018) with a mortality rate of up to 20%.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, until 2004, when the lineage 2 strain was isolated for the first time in Hungary, only lineage 1 strains were circulating. Since then, lineage 2 strains have been isolated in humans and animals in several countries (Kutasi et al, 2011;Hernández-Triana et al, 2014, Barzon et al, 2015, Dinu et al, 2015, being already responsible for dozens of human deaths.…”
Section: Introductionmentioning
confidence: 99%